1987
DOI: 10.7326/0003-4819-106-4-546
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Stenosis and Sclerosing Cholangitis in the Acquired Immunodeficiency Syndrome

Abstract: Eight homosexual men with the acquired immunodeficiency syndrome (AIDS) presented with clinical, biochemical, and radiologic features of stenosis of the papilla of Vater and sclerosing cholangitis. This newly recognized complication of AIDS produces abdominal pain, nausea, and vomiting and may predispose patients to superimposed bacterial cholangitis. Marked elevation of serum alkaline phosphatase levels and lesser changes in hepatic aminotransferase levels are common. Although abdominal ultrasonography and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(44 citation statements)
references
References 12 publications
1
41
1
1
Order By: Relevance
“…This may be responsible for the increase in the serum liver enzymes in the infected patients. As a support to our findings, various studies have shown a significant increase in the serum AST, ALT and the ALK-P activities in the ART naive, HIV positive cases as compared to the control subjects [26][27][28].…”
Section: Methodssupporting
confidence: 79%
“…This may be responsible for the increase in the serum liver enzymes in the infected patients. As a support to our findings, various studies have shown a significant increase in the serum AST, ALT and the ALK-P activities in the ART naive, HIV positive cases as compared to the control subjects [26][27][28].…”
Section: Methodssupporting
confidence: 79%
“…20,21 In spite of severe immunosuppression in the marrow transplant population, cholangitis due to cryptosporidiosis has not been previously reported. Case 4 had colitis secondary to cryptosporidium with intrahepatic biliary strictures that resolved after restoration of cell-mediated immunity and 1 year of treatment with spiramycin.…”
Section: Discussionmentioning
confidence: 99%
“…Papillitis with intra-and extrahepatic biliary strictures secondary to CMV has been reported in other immunocompromised patient populations but rarely in marrow transplant recipients. [17][18][19][20][21] In case 5, although CMV was never isolated from the biliary tree because of ganciclovir treatment, 22 the clinical and cholangiographic images were typical of CMV. In the past, CMV was a common opportunistic infection occurring in up to 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nonspecific hepatic inflammatory changes including mononuclear cell infiltrates or fibrosis in the portal triads, and swollen hepatocytes with vacuolated cytoplasm in~ dicative of chronic hepatocellular injury that were also observed in our population, have also been frequently noted in HIV-infected adults.l,J Biliary tract disease is recognized as a complication of AIDS in adults. & 1~1 5 The prevalence of gallbladder and bile duct abnormalities on sonography has been reported to be as high as 50%.11 Abnormalities of the biliary tract include dilatation and wall thickening of the gallbladder, and dilatation, irregularity, and stricture of the intra-and extra-hepatic bile ducts. Bile duct dilatation is most likely related to acalculous inflammation of the biliary tract caused by the im- Chronic hepatocellular injury Normal mune deficiency itself or to secondary infection by opportunistic infections that typically involve the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%